The Effect Of Preference As A Mediating Variable On Perceived Usefulness And Perceived Ease Of Use Towards The Use Of Mobile Banking In E-Commerce Study On Students In Malang City - Nadia Ariba; Yayuk Sri Rahayu (Journal of Islamic Economy, 2025)
The purpose of this study is to examine how students in Malang City use mobile banking for e-commerce in relation to perceived utility and perceived ease of use, using preference as a mediating variable. A survey technique combined with a quantitative approach is the methodology employed. Purposive sampling was used to choose 100 students who actively utilize mobile banking for the study sample. A questionnaire measuring the characteristics of preference, use, perceived utility, and perceived ease of use of mobile banking was used to gather data. Partial Least Squares-Structural Equation Modeling (PLS-SEM) was used to analyze the data and determine how the variables related to one another. The findings demonstrated that preference has a significant impact on the use of mobile banking in e-commerce, perceived usefulness has a significant impact on preference, perceived ease of use has a significant impact on preference, and perceived usefulness has a significant impact on e-commerce mobile banking use. However, perceived ease of use has no significant impact on e-commerce mobile banking use. The use of mobile banking in e-commerce is significantly impacted by perceived usefulness, which is somewhat mediated by preference. The adoption of mobile banking in e-commerce is heavily influenced by perceived ease of use, which is entirely mediated by preference. These results highlight how crucial it is for service providers to comprehend user preferences in order to enhance the advantages and The adoption of mobile banking in e-commerce is heavily influenced by perceived ease of use, which is entirely mediated by preference. These results highlight how crucial it is for service providers to comprehend customer preferences in order to enhance the advantages and usability of mobile banking